A Rendezvous Scheme for Self-Organizing Cognitive Radio Sensor Networks - Junhyung Kim; Gisu Park; Kijun Han (International Journal of Distributed Sensor Networks)
Two or more nodes need to establish a link on an available channel in a cognitive radio (CR) sensor network when they want to transmit data. Rendezvous is the process by which the nodes explore the available channels to establish a link when they want to communicate with each other. The method of finding a common channel is a challenging problem. A dedicated common control channel simplifies the rendezvous process, but it may create a single point of failure. In this paper, we propose a hopping sequence algorithm to provide an effective method to implement a rendezvous without relying on a dedicated control channel. Our scheme achieves a successful rendezvous within a single period in a CR sensor network. Analytical and simulation results show that our proposed scheme outperforms the existing schemes in terms of time to rendezvous, fairness, degree of overlapping, and the effect by primary user appearance.